La religiosidad popular como factor de identidad en el interior rural de Uruguay: El caso de Santa Teresita en Chamizo (1907-1960). - CASTIGLIA, Pablo (Humanidades: Revista de la Universidad de Montevideo)
The article analyzes how popular religiosity became a factor of identity in rural Uruguay, specifically in the case of Santa Teresita in Chamizo. Despite the secularizing impulse in the country, devotion to Santa Teresita generated a lasting bond between the Chamizo community and the saint. The importance of building a chapel and founding a school in the consolidation of this identity is highlighted. Devotion to Santa Teresita spread nationally and internationally, strengthening the community's identity.